2017
DOI: 10.1016/j.biopsycho.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Is the link between depressed mood and heart rate variability explained by disinhibited eating and diet?

Abstract: Consistently it has been reported that a depressed mood and low heart rate variability (HRV) are linked. However, studies have not considered that the association might be explained by dietary behaviour. The resting inter-beat interval data of 266 adults (Study 1: 156 (51M), Study 2: 112 (38M)) were recorded for six minutes and quantified using linear (HF power: 0.15-0.4Hz) and nonlinear indices (Sample entropy). Participants also completed the Profile of Mood States and the Three Factor Eating questionnaires.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…They concluded that vagal–cardiac control reflected the strength of self-regulation such that successful restrained eaters were characterized by higher cardiac vagal control. These findings are in line with two studies that found reduced HR variability and complexity (R–R interval, HF power, sample entropy) in those with a propensity towards disinhibited eating, which is a tendency to overeat in the presence of palatable foods or other disinhibiting stimuli, such as emotional stress ( Young and Watkins, 2016 ; Young et al , 2017a ). Importantly, these effects remained after controlling for the healthiness of the diet.…”
Section: Heart-rate Variability and Eating Behavioursupporting
confidence: 92%
See 2 more Smart Citations
“…They concluded that vagal–cardiac control reflected the strength of self-regulation such that successful restrained eaters were characterized by higher cardiac vagal control. These findings are in line with two studies that found reduced HR variability and complexity (R–R interval, HF power, sample entropy) in those with a propensity towards disinhibited eating, which is a tendency to overeat in the presence of palatable foods or other disinhibiting stimuli, such as emotional stress ( Young and Watkins, 2016 ; Young et al , 2017a ). Importantly, these effects remained after controlling for the healthiness of the diet.…”
Section: Heart-rate Variability and Eating Behavioursupporting
confidence: 92%
“…Evidence suggests that lifestyle may be one such factor. Young et al (2017a) reported that smoking cigarettes and drinking alcohol negatively influenced HRV, measured using linear (HF power) and nonlinear (sample entropy) measures. In addition, these aspects of the HR time series were increased in those who took regular exercise and consumed a healthy diet.…”
Section: Heart-rate Variability and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…iRBD, idiopathic rapid eye movement sleep behavior disorder; OH, orthostatic hypotension; HRV, heart rate variability. alcohol, caffeine, or to smoke the night before the experiment because these substances could affect the autonomic nervous system (40). The experiment was conducted between 2 p.m. and 4 p.m. to minimize the effect of the circadian rhythm on HRV (41).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…In patients with MDD, Borrione and colleagues [13] found that decreased HRV was associated with specific depressive symptoms, such as guilt, loss of pleasure in activities, and psychomotor retardation. In a study examining two samples of healthy young adults, the association between depressed mood and low HRV was mediated by habitual dietary patterns and disinhibited eating behaviors, respectively [14]. Additionally, although the association between depression and HRV was once thought to be driven by antidepressant medications [15][16][17], a recent study has demonstrated the association is exhibited without the effect of antidepressant medication [18].…”
Section: Introductionmentioning
confidence: 99%